Impact of Electron Radiation Dose to the Performance of Half-Wave Rectifier and Converter Circuits with Silicon Carbide Schottky Diode - Nurul Fazlin Hasbullah; Nafiz ‘Irfan Shuhaimi; Yusof Abdullah; M A Khairi (IAES Indonesian Section, 2020)
Half-wave rectifier; buck; and boost converter with electron-irradiated, high-voltage silicon carbide Schottky power diodes from CREE, Inc., performance were studied and presented in this paper subjected to electron radiation. The diodes were irradiated by high-energy (3 MeV) electrons with doses ranging from 1 to 5 MGy. The performance of the circuits in term of the output voltage were measured before and after the diodes being irradiated. It was observed, at 4 MGy, the half-wave rectifier output voltage degrades by 6.2 times as compared to before irradiation. Meanwhile, the output voltage of the buck converter degrades by 1.7 times; and for boost converter, the degradation of the output voltage is approximately 4.6 times for 4MGy radiation. These degradations are believed to be due to the increase in the series resistance of the Schottky diodes which is caused by the defects introduced inside the semiconductor during the irradiation and also the increase of turn-on voltage of the diodes after being irradiated.